Penerapan Model Project Based Learning di Sekolah Dasar: Hambatan dan Solusi pada Pembelajaran Sains dan Lingkungan Sosial - Ia Dahlia Syahlan; Dede Rahmat Hidayat; Otib Satibi Hidayat (Postgraduate, University of Mataram, 2023)
The Project Based Learning (PjBL) model has been widely applied in elementary schools. However, in practice, not a few teachers and students encounter obstacles when implementing the PjBL model. This research was conducted with the aim of identifying, compiling and describing studies regarding the obstacles in implementing the PjBL model in elementary schools and their solutions. This research is a library research. Researchers collected data from books and 40 articles related to the implementation of the PjBL model in elementary schools. Data analysis was performed using content analysis techniques. The results of the research show the fact that there are obstacles in implementing the PjBL model in elementary schools. These obstacles are: (1) poor time management; (2) teachers and students do not understand the essence of PjBL; (3) lack of motivation of teachers and students; (4) teachers and students have not been able to understand the relationship between PjBL and real life; (5) the inequality in the ability of students in groups makes the project implementation not run smoothly; (6) teachers are confused about adapting learning to the PjBL model, in other words the teacher is not able to understand when PjBL should be implemented; (7) lack of training for elementary school teachers on the PjBL model; and (8) inadequate facilities. At the end of the article, the researcher presents alternative solutions that can be further considered by teachers, schools and curriculum designers to overcome problems that occur during the implementation of PjBL in elementary schools